Corporate workout: the corporate debt restructuring committee revisited - Azmi, Ruzita; Abd Razak, Adilah (Chase Cambria Company (Publishing) Limited, 2015)
A corporate workout is described as financial rescue of a company in distress which takes place outside the limits of insolvency law. According to Belcher a workout is 'the restructuring of the terms of a companys debt contracts to remedy or avoid default achieved by private negotiations with its creditor outside formal bankruptcy or insolvency proceedings.' A corporate workout includes arrangements or negotiations between the corporate debtor and its creditor/bankers outside the formal rescue process and such informal workout covers arrangements to obtain financial investments or rescheduling or restructuring of debts. Such workout is normally arranged by the company’s leading banks, but sometimes also involves major shareholders, bondholders, clients and suppliers, who have a direct interest in the continued existence of the company. The concept of 'workout' involves 'restructuring' of the company’s operations, structure, business, workforce or terms of company’s debt as the company responds to the corporate crisis.